Puppets of nostalgia : the life, death, and rebirth of the Japanese Awaji ningyo tradition - Law, Jane Marie (Princeton legacy library., 1997)
Puppets of Nostalgia is the first major work in any Western language to examine the ritual origins and religious dimensions of puppetry in Japan. In a lucid and engaging style accessible to the general reader, Jane Marie Law describes the ""life, death, and rebirth"" of awaji ningyo shibai, the unique form of puppet theater of Awaji Island that has existed since the sixteenth century. Puppetry rites on Awaji helped to maintain rigid ritual purity codes and to keep dangerous spiritual forces properly channeled and appeased. Law conducted fieldwork on Awaji, located in Japan's Inland Sea, over.